Peace processes, training processes horizontals and a decolonial look. - Figueroa Galván, Nashyeli; Celis Bandala, Adriana (Cinzontle, 2024)
Historically as a Westernized, heteronormative, colonialized society, human ties have been built from an individualizing stance, reifying relationships between people, naturalizing violence. However, reflections and spaces have been generated that seek to strengthen peaceful awareness and action, both ethical and human responsibility, such as training processes in social relationships; That is, they not only involve dynamics within educational institutions, but also the way we live every day. We want to reflect and position ourselves based on the possibilities and tools that promote the construction of peace processes and training processes with a decolonial perspective.
Keywords: violences; peace processes; training processes; decoloniality